Multimédia: um conceito em evolução - Ana Amélia Carvalho Amorim (Universidade do Minho, 2002)
This paper focuses on the multimedia concept and its evolution due to technological development. We refer to three phases in multimedia, and we identify and characterize the components that are relevant to the multimedia concept in the field of education. Then, we describe the theoretical contributions to multimedia in learning. Finally, we distinguish between multimedia and hypermedia, focusing on their scope and convergence.